2020
DOI: 10.3390/app10041526
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Use of Different Sizes of an Ergonomic Instrument Handle for Laparoscopic Surgery

Abstract: Previous studies have shown that the handle design of laparoscopic instruments is crucial to surgical performance and surgeon’s ergonomics. In this study, four different sizes of an ergonomic laparoscopic handle design were tested in a blind and randomized fashion with twelve surgeons. They performed three laparoscopic tasks in order to analyze the influence of handle size. Execution time, wrist posture, and finger and palm pressure were evaluated during the performance of each task. The results show a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…However, in both cases these devices are difficult to integrate into the surgical environment, and are relegated mainly to experimental studies. This technology has been used to objectively study the surgeon's wrist posture in the use of new handle designs for laparoscopic instruments [20].…”
Section: Motion Tracking System Based On Inertial Sensors Placed On the Surgeon's Body (Left) A Biomechanical Model Of The Subject Is Crementioning
confidence: 99%
See 1 more Smart Citation
“…However, in both cases these devices are difficult to integrate into the surgical environment, and are relegated mainly to experimental studies. This technology has been used to objectively study the surgeon's wrist posture in the use of new handle designs for laparoscopic instruments [20].…”
Section: Motion Tracking System Based On Inertial Sensors Placed On the Surgeon's Body (Left) A Biomechanical Model Of The Subject Is Crementioning
confidence: 99%
“…In a study, we evaluated the pressure exerted by the surgeon's distal phalanges of the thumb and the index, middle and ring fingers, as well as the palm of the hand during the use of new handle designs for laparoscopic instruments and with different sizes [20]. The participating surgeons performed three laparoscopic basic tasks to analyze the influence of handle size.…”
Section: Human-instrument Interactionmentioning
confidence: 99%
“…They concluded that the use of their ergonomic handle reduced muscle fatigue and improved the ease of use of the instrument. Similarly, Sánchez-Margallo et al [28] compared customized 3D-printed handles with standard handles and reported that the customized handles aided the surgeon's hand-eye coordination and led to shorter execution times.…”
Section: Additive Manufacturing For Surgical Devicesmentioning
confidence: 99%
“…Anyway, the operating field in the context of synergies between engineering and surgery provides most of the advanced and promising solutions. In this regard, further interesting applications are described in the issue: from the control of MRI-compatible robots [25] and the guidance of surgical needles [26], to the use of very complex image analysis methods for surgical tool characterization [27] and the development of novel devices with high functional performances [28] and better ergonomic design for laparoscopic applications [29].…”
Section: About the Present Issuementioning
confidence: 99%